The impact of data quality dimensions on business process improvement - Panahy, Payam Hassany Shariat; Sidi, Fatimah; Affendey, Lilly Suriani; A. Jabar, Marzanah (IEEE (IEEE Xplore), 2014)
Guaranteeing high data quality level is an important issue to increase the efficiency of the business processes. In fact, poor data quality produces wrong information, which leads to the failure of the business process improvement. Identifying data quality problems has positive impact on overall effectiveness and efficiency of the process improvement. In fact, improving data quality often requires modifying business process enriching them with the most improvement activities. Such activities depend and change based on the data quality dimensions. In this paper, we focus on review of the impact of data quality dimensions on business process improvement in order to support managers to facilitate the implementation of process improvement. The evaluations of this research will use to refine and extend knowledge of relationship between data quality dimensions and business process improvement.